2019
DOI: 10.3389/fphy.2019.00168
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Type RK4 Solutions to Fuzzy Hybrid Retarded Delay Differential Equations

Abstract: This paper constructs the numerical solution of particular type of differential equations called fuzzy hybrid retarded delay-differential equations using the method of Runge-Kutta for fourth order. The concept of fuzzy number, hybrid-differential equations, and delaydifferential equations binds together to form our equations. An example following the algorithm is presented to understand the Concept of fuzzy hybrid retarded delaydifferential equations and its accuracy is discussed in terms of decimal places for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Delay differential equations (DDEs): During the last few years, there have been many studies on DDEs. A very special type of retarded delay differential equations called fuzzy hybrid retarded equations are studied in [1]. For these equations, numerical schemes based on Runge-Kutta schemes are a good option to obtain accurate solutions.…”
Section: Analytical and Numerical Methods For Differential Equations And Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delay differential equations (DDEs): During the last few years, there have been many studies on DDEs. A very special type of retarded delay differential equations called fuzzy hybrid retarded equations are studied in [1]. For these equations, numerical schemes based on Runge-Kutta schemes are a good option to obtain accurate solutions.…”
Section: Analytical and Numerical Methods For Differential Equations And Applicationsmentioning
confidence: 99%
“…Thus, in this research topic, readers can find papers on varying numerical methods and applications.Delay differential equations (DDEs): During the last few years, there have been many studies on DDEs. A very special type of retarded delay differential equations called fuzzy hybrid retarded equations are studied in [1]. For these equations, numerical schemes based on Runge-Kutta schemes are a good option to obtain accurate solutions.Recent advances in stochastic or fractional ODEs and PDEs have been published in the last few years.…”
mentioning
confidence: 99%
“…A notable example by Wang et al (2021) showcases the efficacy of machine learning in forecasting electric load in energy systems through the application of a Clifford fuzzy support vector machine [16]. In another stride, Dhandapani et al ( 2019) demonstrated the successful utilization of numerical methods to solve complex fuzzy systems [27]. These instances underscore the transformative potential of harmonizing algebraic modeling, data analysis, and machine learning to analyze, predict, and optimize LA-Semigroup behavior.…”
Section: Exploring Applications and Examples: Mathematical Modeling O...mentioning
confidence: 99%
“…By exploring the properties, relationships, and composition of roughness sets within LA-Semigroups, researchers have deepened their understanding of this field's fundamental characteristics [6,7,26]. Additionally, the integration of data analysis and machine learning perspectives has opened up new avenues for research, enabling the development of predictive models, optimization techniques, and decision-making processes related to LA-Semigroup operations [27]. These advancements provide valuable insights into the efficient utilization and enhancement of LA-Semigroups in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…For the solution of fuzzy Fredholm integral equations of the second kind, Ezzati and Ziari discussed an approach which is based on Bernstein polynomials [14]. Similarly to generalized differentiability of fuzzy differential equations, hybrid retarded delay differential equations were solved numerically by Runge-Kutta method [15,16]. For noninteger order, the interval differential equations were solved in [17].…”
mentioning
confidence: 99%